Générer de la vapeur pour produire de l’électricité dans les centrales nucléaires - Matteo, Laura; Tauveron, Nicolas (Comptes Rendus. Mécanique)
This article provides a brief historical overview of the use of steam in large-scale industrial installations such as nuclear reactors. Different generations of reactors are reviewed, from gas-cooled to water-cooled to liquid metal reactors. New or renewed uses for steam and organic fluid steam are also discussed (cogeneration, heat networks, hydrogen production by electrolysis, thermal seawater desalination, safety systems).